Hábitos de higiene bucal y su influencia sobre la frecuencia de caries dental de los y las estudiantes de la Universidad Nacional de Loja de la modalidad de estudios presencial periodo mayo-julio 2014 - Merchán Cabrera, Andrea Isabel (2014)
Dental caries is one of the most prevalent diseases around the world, affecting 90% of the population. Its appearance was greatly associated with sociocultural, economic, environmental and behavioral factors. To determine the oral hygiene habits and their influence on the frequency of dental caries, as well as to find the dental hygiene habits and to determine the frequency of dental caries. It is a descriptive, transverse and quantitative study, 894 students were selected into inclusion and exclusion criterion sample. The students aged between 18 and 30 years old; the dental history was used as an instrument of data collection, , that was made by the dental detailed information about dental caries and oral hygiene habits, taking into account the most common as tooth brushing, flossing and mouthwash. The frequency of dental caries in students was 79.2%. 65.8% of them brush their teeth three times a day, floss 26% and 38.3% use mouthwash. The students of the National University of Loja show high frequency of dental caries due to the low frequency of tooth brushing, flossing and mouthwash. Future studies should examine other variables involved in better oral health care in that group. KEY WORDS: dental caries, oral hygiene habits, often students.